EVALUATION OF THE CARIES RESISTANCE OF TOOTH ENAMEL ACCORDING TO A STUDY ON THE CHEMICAL COMPOSITION AND MICROSTRUCTURE OF THE TOOTH SURFACE DURING ITS PHYSIOLOGICAL MATURATION - Dmitry A. Domenyuk; Sergey Z. Chukov; Anna G. Arutyunova; Oleg O. Ivanuta; Elena E. Yesaulenko; Sergey V. Dmitrienko (Кубанский научный медицинский вестник, 2019)
Aim. In this research, we aimed to investigate the caries resistance of permanent teeth in children at different dentition periods on the basis of data obtained on the chemical composition and microstructure of the tooth surface at the stage of tertiary mineralization.Materials and methods. We examined 34 premolars without signs of carious lesions, which had been extracted from 11–16 old children following indications for orthodontic treatment, using a high-resolution scanning electron microscope JSM-6610LV (JEOL) equipped with a micro X-ray spectrometer INCA Energy 350XT (Oxford Instruments Analytica, UK). The teeth under study were divided into three groups. The 1st, 2nd and 3rd groups comprised teeth extracted from 11–12, 13–14 and 15–16 year-old children, respectively. In these groups, tooth mineralization continues 6–12, 13–36 and 37–60 months after eruption, respectively.Results. The X-ray microanalysis of the teeth under study in terms of chemical composition (percentage by mass) showed that the surface enamel accumulates increased concentrations of Ca, P, F and demonstrates a higher Ca/P ratio under reduced levels of C, Na, O during mineralization. It is found that, during early stages of physiological maturation, tooth enamel shows morphological signs of hypo-mineralization, as well as a low caries- and acid resistance, due to its insuffi ciently formed prismatic structure, lack of a protective layer, signifi cant permeability and a large number of retention points.Conclusion. The obtained results demonstrate the possibility of applying high-resolution electron microscopy and X-ray microanalysis for the study of dental hard tissues in dental practice. The development and implementation of personalized approaches to the prevention of caries, which are based on the selective use of remineralizing preparations and vitaminmineral supplements, can increase the caries- and acid resistance of tooth enamel at all stages of its physiological maturation.